Transition in modern foreign languages: a longitudinal study of motivation for language learning and second language proficiency. (4th July 2017) - Courtney, Louise
Abstract: The current longitudinal study examines the similarities and differences between primary and secondary foreign language curricula and pedagogy along with the development of motivation for language learning and second language proficiency. Data from 26 English learners of French (aged 10–11) were collected across three times points over a 12-month period. The study employed the use of lesson observations, along with questionnaires and focus group interviews to examine the development of attitudes and motivation. To measure linguistic progression an oral role play task, an oral photo description task, and a free writing task were administered at each time point. The results show that an abrupt shift in pedagogy may negatively influence learner attitudes and motivation in early secondary and, while early language learning does appear to generate positive attitudes to language learning, questions remain as to its effectiveness over the longer term when learners encounter language teaching that appears incongruous with their aims. Learners did make significant linguistic progress across the transition phase as measured by objective and fine-grained measures, which raises the question as to whether it may in fact be assessment practices that account for the reported 'hiatus' in progression across transition rather than lack of actual progress.